Observing Protest from a Place: The World Social Forum in Dakar (2011) - Pommerolle, Marie-Emmanuelle; Siméant, Johanna; Sommier, Isabelle (Protest and Social Movements, 2015)
Social movements throughout the world have been central to history, politics, society, and culture. Observing Protest from a Place examines the impact of one such campaign, the global justice movement, as seen from the southern hemisphere. Drawing upon a collective survey from the 2011 World Social Forum in Dakar, the essays explore a number of vital issues, including the methodological problems of studying international activist gatherings and how scholars can overcome those challenges. By demonstrating the importance of the global justice movement and the role of nongovernmental organizations for participants in the southern hemisphere, this volume is an important addition to the literature on community action.